The Latent Function of Tabuik as Minangkabau Culture and Literature Learning in the Merdeka Belajar Curriculum - Dilta, Salsa Yusari; Erianjoni (Indonesian Research Journal in Education |IRJE|, 2024)
This research aimed to describe the function of Tabuik as a learning subject on Minangkabau culture and literature in the Merdeka Belajar Curriculum at the high school level. This research used a purposive sampling technique to choose 39 informants by using criteria determined by the researchers. In collecting the data, this research used observations, interviews, and documents. Meanwhile, the data analysis technique used the flow model analysis technique with data collection, data reduction, data presentation, and verification. The research results showed that in line with the structural-functional theory, the function was divided into two, which are the manifest, named Tabuik, carried out as a routine traditional ceremony. In contrast, the latent function is Tabuik, which now can be used as a learning subject and is linked to subjects in high school, namely Minangkabau culture and literature.